Use of kaolin and proposal to recover the mined area at Sítio Galo Branco, Ecuador, RN (Research, Society and Development, 2021)
This article aims to present some important aspects of the use of kaolin at Sítio Galo Branco, located in Ecuador, RN, in Seridó, and a proposal for the recovery of the mined area. In addition, to present an approach on the risks that occur in the process of extracting kaolin, the health and safety conditions at work, the impacts generated by the inappropriate practices used and to suggest actions to improve the technical, environmental and socioeconomic performance of this activity. Therefore, as a methodological procedure, a review of the existing literature was carried out that addresses the subject under study, together with technical visits to the region. Finally, it is recommended the need for an effective and efficient public policy to support micro and small miners in the region, as well as actions to recover degraded areas.